2014
DOI: 10.1371/journal.pone.0107904
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory and Proliferative Responses of Human Keratinocytes Exposed to the Sesquiterpene Lactones Dehydrocostuslactone and Costunolide

Abstract: The imbalance of the intracellular redox state and, in particular, of the glutathione (GSH)/GSH disulfide couple homeostasis, is involved in the pathogenesis of a number of diseases. In many skin diseases, including psoriasis, oxidative stress plays an important role, as demonstrated by the observation that treatments leading to increase of the local levels of oxidant species ameliorate the disease. Recently, dehydrocostuslactone (DCE) and costunolide (CS), two terpenes naturally occurring in many plants, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Normal human keratinocytes were established from sun-protected skin of healthy individuals ( n = 4) and cultured as previously reported 47 . Cells were plated at 5000/cm 2 and maintained to 4-d post confluency.…”
Section: Methodsmentioning
confidence: 99%
“…Normal human keratinocytes were established from sun-protected skin of healthy individuals ( n = 4) and cultured as previously reported 47 . Cells were plated at 5000/cm 2 and maintained to 4-d post confluency.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, CS and DCE reduced the 306 IL-22-and IFN-g-induced expression of inflammatory and 307 regulatory genes in keratinocytes, including CCL2 and CXCL10. It 308 was hypothesized that using CS and DCE in PsO therapy the pro-309 inflammatory actions of IFN-g and IL-22 on keratinocytes may be 310 reduced [92].…”
mentioning
confidence: 99%
“…Costunolide (C 15 H 20 O 2 ) is a well-studied natural product that exhibits a broad range of biological activities, including anti-oxidant, anti-inflammatory and anti-tumor effects [7][8][9][10][11]. Interestingly, recent studies demonstrated that costunolide had potent hepatic protective effects.…”
Section: Introductionmentioning
confidence: 99%